Rates of Viral Non-Suppression and Acquired HIV-1 Drug Resistance Emergence among Children during the Sociopolitical Crisis in the Northwest Region of Cameroon: A Call for Improved Monitoring Strategies - Ayokanmi, Mobereade; Fokam, Joseph; Tchidjou, Hyppolite Kuekou; Chenwi, Collins Ambe; Hortense, Gonsu Kamga; Kamgaing, Nelly; Takou, Désiré; Beloumou, Grace Angong; Semengue, Ezechiel; Djupsa, Sandrine; Nka, Alex Durand; Teto, Georges; et al. (Current HIV Research, 2024)
BackgroundVirological failure (VF) among children remains concerning, with high risks of HIV drug resistance (HIVDR) emergence and increased disease progression. Therefore, monitoring of viral non-suppression and emerging HIVDR is crucial, especially in the frame of sociopolitical unrest.ObjectiveThe study sought to determine the prevalence of VF and evaluate the acquired HIVDR and viral genetic diversity among children in the Northwest region of Cameroon during the ongoing sociopolitical crisis.MethodsA cross-sectional facility-based study was conducted among HIV-infected children aged ≤18 years, receiving antiretroviral therapy (ART) in urban and rural settings of Northwest Cameroon, from November 2017 through May 2018. Viral load (VL) was done using the Abbott m2000RealTime. Unsuppressed VL was defined as viral load ≥1,000 copies/ml. HIVDR testing was performed by sequencing of HIV-1 protease-reverse transcriptase at the Chantal Biya International Reference Center (CIRCB) using an in-house protocol. Drug resistance mutations (DRM) were interpreted using Stanford HIVdbv8.5 and phylogeny using MEGAv.6. Data were compared between urban and rural areas with p<0.05 considered statistically significant.ResultsA total of 363 children were recruited, average age of 12 years (urban) and 8 years (rural). VL coverage was 100% in the urban setting and 77% in the rural setting. Overall, VF was 40.5% (39% [130/332] in the urban setting and 41% (13/31) in the rural setting; p=0.45). Overall, viral undetectability (defined as VL<40 copies/ml) was 45.5% (46% (urban) and 45% (rural); p=0.47). Among those experiencing confirmed virological failure and who were successfully sequenced (n=35), the overall rate of HIVDR was 100% (35/35). By drug class, HIVDR rates were 97.1% (34/35) for non-nucleoside reverse transcriptase inhibitors (NNRTIs), 97.1% (34/35) for NRTIs and 17.1% (6/35) for protease inhibitors (22.7% (5/22) in the urban setting and 7.7% [1/13] in the rural setting). CRF02_AG was the most prevalent viral clade (75%), followed by other recombinants (09_cpx, 11_cpx, 13_cpx, 22_01A1, 37_cpx) and pure subtypes (A1, F2, G, H).ConclusionIn this population of children and adolescents living with HIV in a context of socio-political instability in the North-West region of Cameroon, rates of viral non-suppression are high, and accompanied by HIVDR selection. Our findings suggest the need for a more differentiated care of these CAHIV, especially those in these regions faced with significant socio-economic and health impacts due to the ongoing crisis.
Keywords: antiretroviral therapy